Successful Surgical Treatment of Coronavirus Disease 2019 (COVID-19) Vaccination Related Upper Extremity Lymphedema: Case Report - Hyung Hwa Jeong; Dong Jin Kim; Hyunsuk Peter Suh; Chang Sik John Pak; Joon Pio Hong (Archives of Plastic Surgery)
Lymphedema is rare adverse effect of coronavirus disease 2019 (COVID-19) vaccination that has been reported in several studies. We present a case of surgically treated secondary lymphedema after COVID-19 vaccination. The patient presented lymphedema at the upper extremity with no specific history except the COVID-19 vaccination 18 months before the visit. Lymphaticovenous anastomosis and liposuction were performed on the posterolateral aspect of the forearm and the upper arm. The volume of the affected arm was reduced to more than 54% at 8 months postoperatively. With precise surgical planning, secondary lymphedema resulting from COVID-19 vaccination could be successfully treated surgically.